RISK MANAGEMENT OF OCCUPATIONAL SAFETY AND HEALTH IN KRI DOCKING PROJECT USING HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL (HIRARC) METHOD CASE STUDY: PT. PAL INDONESIA - Rega Dinatha Putra; Benny Sukandari; Wihartono Wihartono (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The Republic of Indonesia warship (KRI) is one of the elements of the Integrated Fleet Weapon System, which has an important function in carrying out existing tasks in the defense sector. So that KRI readiness is needed optimally to support the operation to be carried out successfully. One way that is used to prepare the KRI is to carry out routine maintenance through the docking process. But in its implementation, there are still accidents experienced by workers. This research was conducted using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method. HIRARC is a method of hazard identification, risk assessment, and risk control measures. This method is considered more precise and more accurate where the dangers that arise in the docking process are explained from each work activity. This method also provides appropriate control measures for each hazard. Based on the results of this HIRARC analysis, in each work activity docking based on Risk Ranking will be sorted according to the level of Risk Matrix and will be discussed further against high risk and implemented controls. Then the recommendations produced to minimize workplace accidents in the docking process are by elimination, Administration Control and Use of PPE (Personal Protective Equipment). Keywords: HIRARC Method, Docking, PT. PAL Indonesia.